Moisture sorption characteristics of dried Katchamita mango (Mangifera indica L.) slices - Miranda, Joylyn Farinas
The study determined the moisture sorption characteristics of dried Katchamita mango (Mangifera indica L.) slices. Ripe Katchamita mango slices were subjected to osmotic dehyration in 40% w/v sugar solution for 16 hours and subsequently dried in a cabinet dryer at 600C for 10 hours. The dried Katchamita mango slices were also assessed in terms of its water activity value, moisture content, and Yeast and Mold Count for 14-day storage at the three temperatures. Results showed that there was no significant difference between the initial and final water activity values, moisture content, and yeast and molds count of samples at three different temperatures. The moisture sorption isotherm of dried Katchamita mangoes was determined at three temperatures (300C, 400C, 500C) over a relative humidity range of 11.28% to 92.31%. Isotherm curves showed that the sorption characteristics of dried Katchamita mango slices followed type 3 (J-shaped) isotherm. The BET, GAB, and Henderson models were fitted to the experimental sorption data. The goodness of fit of the mathematical models was statistically evaluated by means of the standard error of estimation. The GAB model was found to be the most suitable for the description of the sorption data at three temperatures. The GAB monolayer moisture contents (m0) ranged from 6.34 to 9.65%. From the generated moisture sorption isotherm, it can be inferred that dried Katchamita mango slices should be stored at 300C with relative humidity not exceeding 60% in order to be shelf stable. For storage at 400C and 500C, the relative humidity should not go beyond 70% for the product to be considered stable